Psychometric properties of the state-trait anger expression inventory - STAXI-2 in students of a public university of Lambayeque - Vallejos Valdivia, Claudia Dora (2024)
This study analyzes the psychometric properties of the 49-item State-Trait Anger Expression Inventory - STAXI-2 in its Spanish version authored by Miguel-Tobal, Casado, Cano-Vindel and Spielberger. It was administered to students from a public university in Lambayeque which study’s population was made up of 2,205 male and female university students, enrolled in the 2018-II academic semester. Content validity was carried out with 10 expert judges and the reliability was carried out with a pilot sample of 30 students. The factor analysis (FA) was analyzed with a sample of 285 students selected through non random sampling; with a significance level of 0.05 and a confidence level of 95% (0.95). The validity and reliability of the instrument was reported, according to Aiken's V and Cronbach's Alpha Coefficient, finding good internal consistency. Likewise, the CFA using the least squares estimation method turned out to be good, resulting in three factor model: state anger, trait anger, and anger expression and control. It was concluded that the STAXI-2 is a valid and reliable instrument to assess state anger, trait anger, and anger expression and control in students of a public university in Lambayeque.